Theatre and national identity: the case of kwag-hir of Tivland (2013)
A number of studies in national theatrical discourse have focused on die elements and forms of theatre and its performance as well as comparative discussion of differences in similar and dissimilar theatrical traditions across cultures and nations. Several of these investigations centre on other national and theatrical concerns without addressing the roles these forms play in reinforcing national identity and without necessarily focusing on the substantial potentials inherent in die forms in identifying a people’s identity and promoting and preserving the same. There were four objectives that necessitated die inquisition into this study. The first was to bring to the fore the exemplary manner in which die Tiv nation of Nigeria sustained its identity as an ethnic group among several other colonially created slates. The second was to establish dial die Tiv were able to achieve this through the celebration., sustenance and preservation of Kwag-hir, one of the surviving and indigenous theatrical puppetry traditions in Nigeria. The third was to establish dial fostering a strong national identity enhances a nation, not only in the political sense but culturally, validating the value systems which arc inherent in the traditions of peoples, promoting relations; cross-national, cross-cultural and international which will enhance the unity of Nigeria irrespective of the number of ethnic groups it is made up of. The fourth was to examine how Kwag-hir binds together Tiv identity; the structure and organisation which encapsulate Tiv cosmology, driving belief, behaviour, to the upholding of Tiv ideals. The study engaged concepts on identity in a descriptive and explicative analysis of die Tiv theatre, centring on puppetry (Kwag-hir), a principal and a core cultural theme which in several ways reveal the underlying 'driving belief, behaviour and consistent political and cultural posture of die Tiv. Findings reveal that die informed consciousness that enhanced die resistance of die Tiv to political and religious manoeuvring? remains die underlying tenets of Kwag-hir theartre. This impenetrable posture dial signifies Tiv identity marks them out among several oilier ethnic groups.